EP1301 Minimally-invasive cytoreduction in recurrent endometrial cancer: laparoscopic and uniportal video-assisted thoracoscopic surgery (VATS) combined approach. (1st November 2019) - Bizzarri, N; Meacci, E; Giuliante, F; Ghirardi, V; Scambia, G; Fagotti, A
Abstract : Introduction/Background: Cytoreductive surgery for recurrent abdominal endometrial cancer is typically performed with laparotomy approach. Furthermore, thoracic procedures are usually performed with a thoracotomy approach. Recently, the uni-portal video-assisted thoracoscopic surgery (VATS) has been proposed as the new evolution of VATS, with even less morbidity and faster recovery. Methodology: We present the video of a third abdominal and thoracic recurrence of endometrial cancer, managed with a combined laparoscopic and uni-portal VATS approach. Results: The patient is a 58-year-old woman, who was initially diagnosed with FIGO IB grade-2 endometrioid endometrial adenocarcinoma. 19-months after initial surgery she developed a pelvic recurrence, so underwent robotic colpectomy and removal of left pelvic peritoneal nodules, followed by adjuvant chemotherapy. 17-months later, she developed a single splenic recurrence, for which she underwent robotic splenectomy and subsequent chemotherapy. After 18-months, a PET/CT-scan showed avid uptake in the liver capsule/right diaphragm and a 1 cm non-avid right pulmonary nodule. Diagnostic laparoscopy revealed a right diaphragmatic plaque of disease as the only intra-abdominal site of recurrence. She underwent laparoscopic full-thickness right diaphragm resection (5x3 cm) followed by uni-portal VATS with removal of right pleural nodules, diaphragm defect suturing and an atypical resection of right middle lobe. Operation time was 400 minutes and estimated intra-operative blood loss was 80 mls. No macroscopic residual tumour was present at the end of the surgery. No intra-operative complication was recorded. Post-operatively she developed a small right apical pneumothorax, which did not require any intervention. She was discharged on day 6. Histology confirmed recurrent endometrial cancer in all specimens but in the pulmonary nodule (atypical hyperplasia). Adjuvant chemotherapy was started 18-days after the surgery. She is alive and disease-free at 6 months from the surgery. Conclusion: Minimally-invasive debulking abdominal and thoracic surgery to no residual disease for recurrent endometrial cancer, is feasible and ensure a rapid post-operative recovery to start medical treatment. Disclosure: Nothing to disclose